Leadership Style Enhancing Work Motivation of Civil Servant at General Bureau of the Regional Secretariat of South Papua Province - Jois S Doom; Fitriani Fitriani; Yohanis Endes Teturan (Papsel Journal of Humanities and Policy, 2026)
This study examines the role of leadership style in enhancing the work motivation of Civil Servants (Aparatur Sipil Negara/ASN) at the General Bureau of the Regional Secretariat of South Papua Province. The study is theoretically grounded in Amirullah’s (2017) leadership framework, which emphasizes leader–member relations, task structure, and position power, and Sariani’s (2020) motivation theory, focusing on educational background, personal expectations, and job satisfaction. A qualitative descriptive approach was employed to capture in-depth perspectives on leadership practices and motivational dynamics within a newly established provincial government organization. Data were collected through observations, in-depth interviews, and document analysis. A total of 22 informants, comprising senior officials, section heads, and staff members, were purposively selected based on their institutional roles and direct involvement in organizational processes. The findings indicate that leadership style significantly influences employees’ work motivation. Effective leadership is reflected in open and transparent communication, participatory decision-making, clear task delegation, consistent supervision, and fair recognition of employee performance. Moreover, job satisfaction, clarity of work roles, coordination across organizational units, availability of work facilities, and opportunities for capacity building emerged as critical supporting factors in sustaining motivation. The study concludes that a communicative, participative, and supportive leadership style is essential for strengthening work motivation and improving organizational effectiveness in public sector institutions, particularly within developing regional government contexts.